Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s13277-013-1128-x
|View full text |Cite
|
Sign up to set email alerts
|

Murine double minute 2 rs2279744 polymorphism and hepatocellular carcinoma risk in East Asians: a meta-analysis

Abstract: Murine double minute 2 (MDM2) is a crucial negative regulator of p53 function through several mechanisms. There are many studies performed to assess the association between MDM2 rs2279744 polymorphism and hepatocellular carcinoma risk, but the impact of MDM2 rs2279744 polymorphism on hepatocellular carcinoma in East Asians is unclear owing to the inconsistent findings from previous studies. We conducted a comprehensive meta-analysis of epidemiological studies to shed some light on these contradicting results. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Also, Liu et al . concluded that the variant allele 309G was associated with a significantly increased risk of hepatocellular carcinoma in East Asians, which is similar with our current finding . Interestingly, Chen et al .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Also, Liu et al . concluded that the variant allele 309G was associated with a significantly increased risk of hepatocellular carcinoma in East Asians, which is similar with our current finding . Interestingly, Chen et al .…”
Section: Discussionsupporting
confidence: 92%
“…As expected, this presumption was proved by our further investigations, which demonstrated that the G allele of MDM2 SNP309 was positively associated with increased EC risk. Many investigators also have reported similar observations in other cancers . Recently, Qin and colleagues found that the MDM2 SNP309 polymorphism might contribute to colorectal cancer risk, especially in Asian populations .…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…MDM2 SNP309 plays a major role in the carcinogenesis of HCC, especially among Caucasian populations [29]. The findings from different areas support that MDM2 is significantly associated with increased risk of hepatocellular carcinoma [3235]. MDM2 SNP309 G allele is a susceptibility gene for the development of viral hepatitis-related hepatocellular carcinoma [3638].…”
Section: Discussionmentioning
confidence: 99%